Review: Insights on Current FDA-Approved Monoclonal Antibodies Against Ebola Virus Infection - Tshiani Mbaya, Olivier; Mukumbayi, Philippe; Mulangu, Sabue (Frontiers in Immunology, 2021)
1 Abstract The devastating Ebola outbreak in West Africa in 2013-2016 accelerated the progress of several medical countermeasures (MCMs) against Ebola virus disease (EVD). Several IPs were used during that outbreak, but no conclusion on efficacy could be drawn. Only the Randomized Controlled Trial (RCT) on ZMapp was promising but inconclusive. More recently, during the second largest Ebola outbreak in North Kivu and Ituri provinces, Democratic Republic of the Congo (DRC), four IPs (Remdesivir, Regeneron, ZMapp and MAb114) have been evaluated in a RCT, the Pamoja Tulinde Maisha (PALM) study. Two products (Regeneron and MAb114) demonstrated efficacy as compared to the control arm, ZMapp. Very few side effects have been reported. Results from this scientifically sound study led the FDA to license both products, representing a milestone in EVD therapeutic field. These products can be produced relatively inexpensively and can be stockpiled. The administration of mAbs on EVD patients appears to be safe and effective while several important knowledge gaps remain; the impact of early administration of Ebola-specific mAbs on the development of a robust immune response for future Zaire Ebolavirus (EBOV) exposure is unknown. Also, potential viral escape leading to resistance, bioengineering improvement (bispecific mAbs development) of mAbs should be explored. Understanding the contribution of Fc-mediated antibody functions (ADCC) of those approved mAbs is still critical. The potential merit of combination therapy and post-exposure prophylaxis (PEP) need to be demonstrated. Furthermore, the PALM trial has accounted for 30% of mortality despite the administration of specific treatments. The putative role of EBOV soluble Glycoprotein (sGP) as a decoy to the immune system, the virus persistence, and/or relapses might be interrogated for treatment failure. The development of pan-filovirus or pan-species mAbs remains important for protection. The interaction between FDA-approved mAbs and vaccine remain unclear and needs to be investigated. In this review, we summarize the efficacy and safety results of the PALM study and review ongoing research questions in further development of mAbs for pre-exposure or emergency post-exposure use.